1988
DOI: 10.1001/archderm.1988.01670040035018
|View full text |Cite
|
Sign up to set email alerts
|

Papillon-Lefèvre Syndrome Ultrastructural Study and Successful Treatment With Acitretin

Abstract: Four siblings affected by Papillon-Lefèvre syndrome (PLS) ranged in age from 2 to 11 years. The parents were unaffected and parental consanguinity was present. The 2-year-old girl showed the early manifestations of PLS; that is, slight gingival swelling and erythema occurring simultaneously with minimal scaling of palms and soles. The other siblings, aged 5, 8, and 11 years, showed severe periodontopathy with tooth loss and marked palmoplantar keratoderma with a centripetal extension of the keratoses to the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 14 publications
2
25
1
3
Order By: Relevance
“…Furthermore, some authors believe that if treatment is started at an early age, patients would possibly have normal adult dentition [55]. One of the studied cases (7P) is only 18-months-old, and will be under treatment and observation to avoid serious complications.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some authors believe that if treatment is started at an early age, patients would possibly have normal adult dentition [55]. One of the studied cases (7P) is only 18-months-old, and will be under treatment and observation to avoid serious complications.…”
Section: Discussionmentioning
confidence: 99%
“…commun.]. In Papillon-Lefèvre syndrome, ultrastructural studies have revealed lipid-containing vacuoles in stratum corneum cells [21]. It seems speculative to relate the decreased amounts of total ceramides or the increased level of free sterols to these stratum corneum lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Les lésions érythèmato-squameuses palmoplantaires sont diffuses, symétriques, bien limitées, plus ou moins fissuraires, et plus ou moins épaisses. Cette KPP est extensive et transgrédiente débordant sur les faces laté-rales et dorsales des mains et des pieds, sur le tendon d'Achille et sur les malléoles externes [106,136]. Des placards érythemato-kératosiques psoriasiformes peuvent être observés au niveau des coudes et des genoux [106,136], plus rarement au niveau des jambes, des bras, du tronc [106], ou au niveau des pavillons des oreilles et des conduits auditifs externes [106].…”
Section: Le Syndrome De Papillon-lefèvreunclassified
“…Une hyperhidrose palmoplantaire malodorante est fréquente, parfois il existe une anhidrose. Des lésions unguéales ont été rapportées, à type d'onychodystrophie, d'onychogryphose, de striations transversales ou longitudinales et de ponctuations unguéales [106].…”
Section: Le Syndrome De Papillon-lefèvreunclassified
See 1 more Smart Citation